1996
DOI: 10.2307/1243715
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Farm‐Level Crop Insurance Demand with Panel Data

Abstract: A random-effects, binomial probit model is applied to data for a panel of Kansas wheat farms to examine Multiple Peril Crop Insurance demand. A theoretical model is developed which suggests inclusion of the moments of both market return and the return to insurance. Empirical results indicate that the first and second moments of both market return and the returns to insurance are significant. The price elasticity of demand is estimated to be −0.65. Preseason weather variables when included in the models were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
75
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(78 citation statements)
references
References 7 publications
0
75
0
3
Order By: Relevance
“…A multinomial discrete choice model of crop insurance participation and whether to opt for yield or revenue insurance is developed building on the participation model developed by Coble et al (1996). To model the unordered choices of participation, yield, and revenue insurance, we assume producers maximize expected utility according to a von Neuman-Morgenstern utility function defined over wealth (W).…”
Section: A Model Of Yield and Revenue Insurance Participationmentioning
confidence: 99%
See 2 more Smart Citations
“…A multinomial discrete choice model of crop insurance participation and whether to opt for yield or revenue insurance is developed building on the participation model developed by Coble et al (1996). To model the unordered choices of participation, yield, and revenue insurance, we assume producers maximize expected utility according to a von Neuman-Morgenstern utility function defined over wealth (W).…”
Section: A Model Of Yield and Revenue Insurance Participationmentioning
confidence: 99%
“…While on average, the program was paying out more than a dollar for every dollar producers paid in premiums, the participation rate was relatively low. Research by Coble et al (1996) and Goodwin and Smith suggested that the program was likely affected by adverse selection, such that program participants were earning significant positive returns while nonparticipants perceived that they would not receive a benefit, either in terms of expected return or risk reduction, sufficient to justify the premium.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Babcock andHart, 2005 andDonoghue, 2014), risk frequency (e.g. Coble et al, 1996), asymmetric information (e.g. Zilberman, 2008 andGlauber et al, 2002) or farmers characteristics (Santeramo et al, 2016a).…”
Section: Agricultural Insurance System Sustainability and Risk Predicmentioning
confidence: 99%
“…More detailed analyses of demand for crop insurance, i.e. the factors which really affect the purchase of insurance and future demand forecasts are usually focused on other markets, mainly in the US [Coble et al 1996;Goodwin, Vandeveer, Deal 2004;Mishra, Goodwin 2003;Sherrick et al 2004;Garrido, Zilberman 2008;Ogurtsov, Van Asseldonk, Huirne 2009].…”
Section: Risks In the Farms In Poland And Their Financing -Research Fmentioning
confidence: 99%